Respuestas
Respuesta dada por:
2
Expresión algebraica
3+2(n-1)
Cuando n=1
Remplazamos las “n” en la expresión
3+2(1-1)=3+2(0)=3
Cuando n=2
3+2(2-1)=3+2(1)=5
Cuando n=3
3+2(3-1)=3+2(2)=3+4=7
Expresión algebraica
3+[(2)(n)-2]
Cuando n=1
Remplazamos las “n” en la expresión
3+[(2)(1)-2]=3+[0]=3
Cuando n=2
3+[(2)(2)-2]=3+[4-2]=3+2=5
Cuando n=3
3+[(2)(3)-2]=3+[6-2]=3+4=7
Espero te sirva.
3+2(n-1)
Cuando n=1
Remplazamos las “n” en la expresión
3+2(1-1)=3+2(0)=3
Cuando n=2
3+2(2-1)=3+2(1)=5
Cuando n=3
3+2(3-1)=3+2(2)=3+4=7
Expresión algebraica
3+[(2)(n)-2]
Cuando n=1
Remplazamos las “n” en la expresión
3+[(2)(1)-2]=3+[0]=3
Cuando n=2
3+[(2)(2)-2]=3+[4-2]=3+2=5
Cuando n=3
3+[(2)(3)-2]=3+[6-2]=3+4=7
Espero te sirva.
Respuesta dada por:
0
Respuesta:
ni idea ;(
Explicación paso a paso:
Preguntas similares
hace 1 año
hace 1 año
hace 1 año
hace 4 años
hace 4 años
hace 4 años
hace 7 años